Antenatal fetal surveillance "Assessment of the AFV". (January 2017) - Hughes, Dawn S.; Magann, Everett F.
Abstract : The evaluation of amniotic fluid volume (AFV) is an established part of the antenatal surveillance of pregnancies at risk for an adverse pregnancy outcome. The two most commonly used ultrasound techniques to estimate AFV are the amniotic fluid index (AFI) and the single deepest pocket (SDP). Four studies have defined normal AFVs, and although their normal volumes have similarities, there are also differences primarily due to the statistical methodology used in each study. Dye-determined AFV correlates with ultrasound estimates for normal fluid volumes but correlates poorly for oligohydramnios and polyhydramnios. The addition of color Doppler in estimating AFV leads to the overdiagnosis of oligohydramnios. Neither the AFI nor the SDP is superior in identifying oligohydramnios, but the SDP is a better measurement choice as the use of AFI increases the diagnosis rate of oligohydramnios and labor inductions without an improvement in pregnancy outcomes. Highlights: Amniotic fluid volume assessment is essential in high-risk pregnancies. Ultrasound accurately estimates normal amniotic fluid volume but not oligohydramnios or polyhydramnios. Amniotic fluid index overdiagnoses oligohydramnios leading to more labor inductions without improving perinatal outcome. Color Doppler does not improve the accuracy of identifying actual oligohydramnios. Single deepest pocket is a better measurement than the amniotic fluid index in diagnosing oligohydramnios.